2014
DOI: 10.1111/j.2047-2927.2014.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Are testicular mast cells involved in the regulation of germ cells in man?

Abstract: Protease activated receptor-2 (PAR-2) is the receptor for the prototype mast cell product tryptase. PAR-2 expression by cells of the human germinal epithelium was reported, but the exact cellular sites of testicular expression remained unknown. That became of interest, because mast cells, expressing tryptase, were found in the walls of seminiferous tubules of patients suffering from sub-and infertility. This location suggested that mast cells via tryptase might be able to influence PAR-2-expressing cells in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 40 publications
0
19
0
2
Order By: Relevance
“…In addition to BTB and anatomical impairment of external cells' and molecules' entrance to testis, SCs also provide anti-inflammatory mediator secretion aiming to maintain the tolerogenic microenvironment [8]. However, many local immune modulators, including macrophages, dendritic cells (DCs), natural killer cells (NKs), mast cells and T-lymphocytes, contribute to the intercommunication among testicular components [9][10][11][12]. The testis is composed of interstitial LCs located between blood vessels and the seminiferous tubules, where sperm is produced [25].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to BTB and anatomical impairment of external cells' and molecules' entrance to testis, SCs also provide anti-inflammatory mediator secretion aiming to maintain the tolerogenic microenvironment [8]. However, many local immune modulators, including macrophages, dendritic cells (DCs), natural killer cells (NKs), mast cells and T-lymphocytes, contribute to the intercommunication among testicular components [9][10][11][12]. The testis is composed of interstitial LCs located between blood vessels and the seminiferous tubules, where sperm is produced [25].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a possible trophic action of MCs in seminiferous tubules of infertile cases was mentioned by Windschuttl et al . () possibly by secreting tryptase that may influence spermatogonia expressing protease‐activated receptor‐2. In addition, Adam et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that the increased MCs in testicular biopsies of MA and GCA patients are negatively correlated with Johnsen score and Ki67 index but positively correlated with vimentin expression in Sertoli cells. Nevertheless, a possible trophic action of MCs in seminiferous tubules of infertile cases was mentioned by Windschuttl et al (2014) possibly by secreting tryptase that may influence spermatogonia expressing protease-activated receptor-2. In addition, Adam et al (2011) have demonstrated small amounts of the ECM protein decorin (DCN) in the wall of normal seminiferous tubules.…”
Section: Discussionmentioning
confidence: 99%
“…PAR‐2 expressing spermatogonia in seminiferous epithelium could be influenced by tryptase‐releasing MCs . Investigations on TCam‐2 seminoma cells with high expression levels of PAR‐2 showed that tryptase prevents apoptosis and supports their proliferation . Sezer et al reported the elevated expression levels of iNOS in Leydig cells correlate with MC index in Sertoli cell‐only syndrome (SCO) and severe damage of the germ cell .…”
Section: Male Reproduction System Residing Mast Cellsmentioning
confidence: 99%